LA PRÁCTICA PEDAGÓGICA COMO ESCENARIO DE APRENDIZAJE ÉNFASIS EN LA PRIMERA INFANCIA (2023)
This article addresses the problems faced by teachers in training when practicing with early childhood. This problem is divided into two factors, which are: The lack of preparation or training regarding the management of this age range and the lack of methodologies or dynamics at the time of exercising the practice. In order to investigate this problem in more depth, a literature review methodology was used, focusing on twelve articles related to the subject.